Effects of various austempering temperatures on fatigue properties in ductile iron - (:unkn) unknown (ELSEVIER SCI LTD, 2007)
Austempering is an isothermal heat treatment which when applied to ferrous materials, produces a structure that is stronger and tougher than comparable structures produced with conventional heat treatments. In this paper, ductile iron specimens were applied to various austempering temperatures and interpreted fatigue properties. In this test, Denison 7615 fatigue machine was used for doing double sided bending stresses. The iron was austenitized at 900 degrees C and then austempered at 235, 300 and 370 degrees C for 2 h within a salt bath to obtain various austempered microstructures. Also, the fatigue properties of the bainitic; structures which occurred by austempering are examined by scanning electron microscope. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CYCLE FATIGUE; CAST-IRON; MICROSTRUCTURE